Taxation of the Public Sector in Poland - Huchla, Andrzej (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
There is no system of taxation of the public sector in Poland. Acts of tax law even don`t use the general term "public sector”. Therefore, its position in the sphere of taxation must be analyzed through the detailed provisions of each tax separately. Such rules can be found in the tax on goods and services (VAT), in the corporate income tax as well as in real estate taxes. Public bodies are often, directly or not, freed from taxation by differently constructed tax exemptions. Perhaps it is possible to prove that there is some general trend not to tax public sector subjects. However, relevant provisions are fragmentary and incoherent.
Keywords: podatki; sektor publiczny; Polska